Animal models of ischemic heart disease for in vivo cardiac MR imaging research. (26th April 2010) - Feng, Yuanbo; Xie, Yi; Chen, Feng; Wang, Huaijun; Li, Junjie; Jin, Lixin; Dymarkowski, Steven; Yu, Jie; Jiang, Yansheng; Peeters, Ronald; Marchal, Guy; Ni, Yicheng
A variety of experimental models of coronary artery occlusion can be used to study basic mechanisms and clinical aspects of ischemic heart disease and play therefore a central role in modern cardiac research. Cardiac magnetic resonance imaging (cMRI) techniques have recently been developed to quantify or semi-quantify in vivo cardiac anatomy, ventricular function, blood flow perfusion, myocardial infarction and metabolism. With these techniques, the normal or abnormal animal heart has been shown to be well suited as a model of human cardiac diseases. Non-invasive in vivo cMRI in animals may provide a unique and powerful means for phenotyping genetically engineered animals and can improve our understanding of the roles of specific genes and proteins in cardiac physiology and pathophysiology. A practical understanding of the choice, care and use of animal models under the preclinical framework is expected and required for those involved biomedical researchers. The role of individual animal models of ischemic heart disease in cMRI research has been reviewed in this article. Furthermore, a new modified rabbit model of myocardial ischemia developed in our laboratory has also been introduced.